Literature and Bullying: Teenage and Children Novels on School Bullying Prevention - Raptou, Evangelia (International Journal of Criminology and Sociology, 2017)
Juvenile delinquent or deviant behavior appears in various forms in modern academic reality. It is widely known under the international term "school bullying". The systemic view of an educational organization as it studies the variety of school and social system parameters that explain and contribute to the emergence of problematic behaviors in schools positively contributes to a better understanding of that behaviors considered within the framework of interactions that generate and reproduce it. Qualitative literary works, by which this phenomenon is approached in a novel way and the "omnipotent narrator" dominates, provide the possibility of a holistic and systemic view and indirect aids in strategies for preventing, detecting and curing the offending incidents in modern schools. The purpose of this paper is to connect the phenomenon of bullying appearing in teenage and children novels with the way that texts could illuminate and enlighten youth consciousness in order to become safe guides or useful paradigms in their everyday life. The texts examined under present study are the novels (a) Thirteen Reasons Why, by Jay Asher (b) Finding Audrey, by Sophie Kinsella and (c) Together, by Eleni Priοvolou.